Full-tab cylindrical winding core, lithium ion battery and electric device

CN122659331APending Publication Date: 2026-08-28JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129506.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

若金属层覆盖长度、厚度和胶带覆盖关系不匹配,金属层端部可能在外圈挤压、跌落冲击或热胀冷缩过程中接近活性物质层边缘、壳体或其他导电部件,增加局部短路风险

Benefits of technology

[0022] This invention has the following beneficial effects: The invention uses the tail-covering-radial pre-tightening coordination coefficient Kp to simultaneously constrain the covering arc length, tape width, expansion rate, and radial allowance within the shell, ensuring that the outer ring tail fixing and radial pre-tightening are in a matched state. By adjusting the range of Kp, the axial displacement of the core and radial loosening of the outer ring after a drop can be reduced. The metal tailing-space utilization coordination coefficient Km constrains the covering length and thickness of the metal tailing layer, allowing the copper foil or metal composite layer to save space and assist in heat diffusion in the outer ring tailing, without occupying too much radial allowance within the shell or introducing the risk of end short circuits due to excessive metal layer thickness or excessive coverage. By introducing carbonaceous thermally conductive fillers and simultaneously controlling the volume resistivity, thermal conductivity, S2, and S1, the black thermally conductive/conductive tailing tape maintains the necessary insulation boundary while improving outer ring heat diffusion, reducing the risk of short circuits caused by excessive interconnection of fillers such as carbon black, graphite, or carbon nanotubes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659331A_ABST
    Figure CN122659331A_ABST
Patent Text Reader

Abstract

The application discloses a full-tab cylindrical winding core, a lithium ion battery and an electric equipment, and relates to the technical field of lithium ion batteries. The arc length, the width of the adhesive tape, the expansion rate and the radial allowance in the shell are simultaneously constrained by Kp, so that the end fixing of the outer ring and the radial pre-tightening are in a matching state. The range of Kp is adjusted to reduce the axial displacement of the winding core and the radial looseness of the outer ring after falling. The covering length and the thickness of the metal end layer are constrained by Km, so that the copper foil or the metal composite layer can save space in the end of the outer ring and assist heat diffusion, and the metal layer will not be too thick or too long to occupy too much radial allowance in the shell or introduce the risk of end short circuit. By introducing carbon heat-conducting fillers, the volume resistivity, the thermal conductivity, S2 and S1 are adjusted, so that the black heat-conducting / electrically-conducting end adhesive tape can maintain the necessary insulation boundary when improving the heat diffusion of the outer ring, and the risk of short circuit caused by excessive connection of carbon black, graphite or carbon nanotube fillers can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a full-tab cylindrical core, a lithium-ion battery, and an electrical device. Background Technology

[0002] Full-tab cylindrical lithium-ion cells typically consist of a core formed by winding a positive electrode, a separator, and a negative electrode, with a flattened tab structure at the axial end of the core to reduce the impedance of the current-collecting path and improve high-rate output capability. For cylindrical cells of the 21650 or 21700 size with a capacity of approximately 5Ah, the outer diameter of the core, the inner diameter of the casing, the length of the electrode, the thickness of the separator, and the flattened tab structure collectively determine the utilization rate of the internal space. As the length of the electrode increases and the core filling density improves, the fixation reliability of the outer ring of the core has a more significant impact on drop resistance, vibration resistance, short-circuit safety, and high-rate heat distribution.

[0003] Currently, most cylindrical battery cores use ordinary terminating tape or diaphragm finishing methods to fix the outer ring. Ordinary finishing tape usually only serves the function of bonding and positioning, and it is difficult to simultaneously take into account the radial pretension of the outer ring, heat diffusion, metal layer insulation clearance, and core displacement control after drop. If the outer ring is not properly fixed, the battery core may experience axial movement relative to the shell, local loosening of the outer ring, tape peeling, or metal edge contact risks after a drop, vibration, or thermal shock. Simply increasing the tape thickness or increasing the bonding area may reduce the radial allowance inside the shell, leading to difficulties in installation, local compression, or stress concentration in the shell.

[0004] In high-capacity omni-tab cylindrical cells, using copper foil or a metal composite layer to terminate the outermost ring of the negative electrode can save space and improve heat dissipation in the outer ring. However, the metal termination layer also introduces issues such as end metal edges, local conductive paths, and short-circuit protection. If the length, thickness, and tape coverage of the metal layer are mismatched, the end of the metal layer may approach the edge of the active material layer, the casing, or other conductive components during outer ring compression, drop impact, or thermal expansion and contraction, increasing the risk of local short circuits.

[0005] Meanwhile, black finishing tape or tape containing carbon black has the potential to improve thermal diffusion, but excessively high content of conductive / thermal fillers will reduce the tape's volume resistivity and weaken its insulation safety boundary; while excessively low filler content will make it difficult to improve the thermal diffusion of the outer ring. Expandable tape or expandable adhesive layer can form radial pretension of the outer ring through liquid absorption expansion, thermal expansion, or compression rebound, but excessively low expansion rate cannot improve drop displacement, while excessively high expansion rate may compress the outer ring of the core or push the end of the metal layer to shift.

[0006] Therefore, there is an urgent need to improve the finishing structure of the all-tab cylindrical core to solve the problems of ordinary finishing tape bonding and fixing, metal finishing layer space utilization, outer ring radial pretension and short-circuit safety boundary in the finishing area of ​​high-capacity all-tab cylindrical core, so as to improve the reliability of drop, vibration and short-circuit safety.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] The purpose of this invention is to provide a full-tab cylindrical core, a lithium-ion battery, and an electrical device to improve safety and reliability in the event of drops, vibrations, and short circuits.

[0009] This invention is implemented as follows: In a first aspect, the present invention provides a cylindrical core with full tabs, including a positive electrode sheet, a negative electrode sheet, and a diaphragm disposed between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet, the diaphragm, and the negative electrode sheet are wound together to form a core, and the axial ends of the positive electrode sheet and the negative electrode sheet form a flattened full tab structure. The outer ring of the core is provided with a composite finishing structure, which includes a composite finishing tape and a metal finishing layer. The composite finishing tape is attached circumferentially to the outer finishing area along the core. The composite finishing tape includes a substrate layer and an adhesive layer. Carbonaceous thermally conductive filler is dispersed in the substrate layer and / or adhesive layer. The volume resistivity of the composite finishing tape at 25°C is 1.0 × 10⁻⁶. 4 Ω·cm ~ 1.0×10 10 Ω·cm, in-plane thermal conductivity greater than or equal to 0.30 W / (m·K); The metal finishing layer is disposed at the outermost ring of the negative electrode sheet or at a position adjacent to the outermost ring of the negative electrode sheet, and at least a portion of the metal finishing layer is covered by composite finishing tape.

[0010] In an optional embodiment, the coverage arc length of the composite finishing tape along the winding direction is L1 (mm); the width of the composite finishing tape is W1 (mm); the thickness of the composite finishing tape before application is t1 (mm); the thickness change rate of the composite finishing tape after being immersed in electrolyte at 25°C for 24 hours and heat-treated at 80°C for 30 minutes is E1 (E1 is a decimal); the maximum outer diameter of the core in the finishing area is D1 (mm); the core height is H1 (mm); half the difference between the inner diameter of the shell and the maximum outer diameter of the core is the radial allowance G1 (mm); the finishing coverage-radial pretensioning coordination coefficient Kp is defined as: Kp=(L1 / (π×D1))×(W1 / H1)×(t1×(1+E1) / G1), and 0.015≤Kp≤0.045; The physical meaning of Kp is the effective constraint ratio of the composite finishing tape expansion pretension on the outer ring of the core. When Kp < 0.015, the tape expansion amount or coverage area is insufficient, and a stable radial flexible pretension cannot be established. After falling, axial movement and circumferential peeling are likely to occur. When Kp > 0.045, the tape expansion thickness ratio is too high, squeezing the radial allowance inside the shell, resulting in increased resistance to entering the shell or the metal layer end being pushed and displaced.

[0011] The coverage length of the metal finishing layer along the winding direction is L2, in mm; the thickness of the metal finishing layer before application is t2, in mm; the metal finishing-space utilization synergy coefficient Km is defined as: Km = (L2 / L1) × (t2 / t1) × (G1 / (t1 × (1+E1))), and 0.15 ≤ Km ≤ 0.95; Km characterizes the spatial matching degree between the metal finishing layer and the tape expansion compensation. Exceeding this range will lead to the interruption of the heat diffusion path or the compression of the insulation boundary.

[0012] There is an insulating clearance distance S2 between the end of the metal finishing layer and the outer edge of the composite finishing tape, and there is an edge insulation distance S1 between the conductive filler enrichment area of ​​the composite finishing tape and the edge of the active material layer of the negative electrode sheet. Both S2 and S1 are greater than or equal to 0.5 mm.

[0013] In an optional implementation, Kp is 0.020~0.045, preferably 0.025~0.040; And / or, L1 is 35mm~120mm; And / or, W1 is 3.0mm~12.0mm; And / or, t1 is 0.020mm~0.120mm; And / or, E1 is 0.05~0.80; And / or, D1 is 20.20mm~20.70mm; And / or, H1 is 64.5mm~67.5mm; And / or, G1 is 0.03mm~0.35mm.

[0014] In an optional embodiment, the material of the substrate layer of the composite finishing tape is selected from at least one of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper and polyamide-imide. And / or, the adhesive layer of the composite finishing tape is selected from at least one of acrylic pressure-sensitive adhesives, silicone rubber pressure-sensitive adhesives, polyurethane adhesives and epoxy modified adhesives; And / or, the carbonaceous thermally conductive filler is selected from at least one of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fiber and acetylene black; the mass content of the carbonaceous thermally conductive filler in the composite finishing tape is 2wt%~25wt%, preferably 5wt%~15wt%.

[0015] In an optional embodiment, the composite finishing tape further includes an insulating and thermally conductive filler, which is dispersed in the substrate layer and / or adhesive layer and can form an insulating barrier region in the area near the end of the metal finishing layer and the edge of the active material layer of the negative electrode sheet; the insulating and thermally conductive filler is selected from at least one of alumina, boehmite, boron nitride, magnesium oxide and silicon oxide. And / or, the in-plane thermal conductivity of the composite finishing tape is 0.30 W / (m·K) to 3.00 W / (m·K), and the thermal conductivity in the thickness direction is 0.15 W / (m·K) to 1.20 W / (m·K).

[0016] In an optional embodiment, the composite finishing tape further includes an expanding adhesive layer, which is disposed between the substrate layer and the adhesive layer, or on the side of the substrate layer away from the adhesive layer; the adhesive layer is located on the side close to the outer ring of the core. Preferably, after the expanded adhesive layer is immersed in an electrolyte at 25°C for 24 hours and then heat-treated at 80°C for 30 minutes, the thickness change rate E1 of the composite finishing tape is 0.10~0.60. Preferably, the expanding adhesive layer contains at least one of the following: liquid-absorbing expanding microparticles, thermally expanding microspheres, elastomer microporous structures, and foamed polymer microregions.

[0017] In an optional embodiment, the material of the metal finishing layer is selected from at least one of copper foil, nickel-plated copper foil, carbon-plated copper foil, aluminum foil, stainless steel foil, nickel foil, and copper-polymer composite foil; And / or, the thickness t2 of the metal finishing layer is 0.004mm~0.030mm, preferably 0.006mm~0.015mm; And / or, the coverage length L2 of the metal tail layer along the winding direction is 30mm~140mm, and the L2 / L1 ratio is 0.50~1.30; And / or, the width of the metal finishing layer along the core axis is less than or equal to the width of the composite finishing tape, and at least one axial edge of the metal finishing layer is recessed by 0.5mm to 5.0mm relative to the corresponding axial edge of the composite finishing tape. And / or, S2 is greater than or equal to 0.6 times S1, and S2 is 0.5mm~6.0mm, while S1 is 0.5mm~6.0mm; when the volume resistivity of the composite finishing tape is less than 1.0×10 6 When the volume resistivity is Ω·cm, both S2 and S1 are greater than or equal to 1.0 mm. When the volume resistivity is 1.0 × 10⁻⁶ Ω·cm... 4 ~1.0×106 At Ω·cm, a thermally conductive network is formed in the tape surface. However, by limiting S2≥1.0mm and S1≥1.0mm, the conductive filler-rich area and the active material are kept in a filler-free transition area, thus achieving a synergistic safety mechanism of 'thermal conduction by in-plane connectivity and insulation by geometric isolation'.

[0018] In an optional implementation, the core is used for 21650 or 21700 model cylindrical lithium-ion cells with a capacity of 4.9Ah to 5.2Ah. And / or, after the core is dropped once from a height of 1.5m in each of six directions at 100% SOC and 25℃, the axial displacement of the core relative to the shell is less than or equal to 0.30mm, and the radial loosening of the core tail area is less than or equal to 0.15mm. And / or, after 2 hours of sweeping vibration from 10Hz to 55Hz, the peel length of the composite finishing tape is less than or equal to 10% of its covering arc length L1.

[0019] In a second aspect, the present invention provides a lithium-ion battery comprising a full-tab cylindrical core according to any of the foregoing embodiments, wherein the full-tab cylindrical core is housed in a cylindrical shell and forms a cylindrical lithium-ion battery together with a cap assembly, an electrolyte and an insulating component.

[0020] In an optional embodiment, the cylindrical lithium-ion battery has an AC internal resistance of 2.4 mΩ to 3.3 mΩ at 1 kHz at 25°C and 30% SOC; and / or, a 10 s DCR of 7.0 mΩ to 10.5 mΩ at 25°C and 100% SOC.

[0021] Thirdly, the present invention provides an electrical device comprising a lithium-ion battery according to any of the foregoing embodiments.

[0022] This invention has the following beneficial effects: The invention uses the tail-covering-radial pre-tightening coordination coefficient Kp to simultaneously constrain the covering arc length, tape width, expansion rate, and radial allowance within the shell, ensuring that the outer ring tail fixing and radial pre-tightening are in a matched state. By adjusting the range of Kp, the axial displacement of the core and radial loosening of the outer ring after a drop can be reduced. The metal tailing-space utilization coordination coefficient Km constrains the covering length and thickness of the metal tailing layer, allowing the copper foil or metal composite layer to save space and assist in heat diffusion in the outer ring tailing, without occupying too much radial allowance within the shell or introducing the risk of end short circuits due to excessive metal layer thickness or excessive coverage. By introducing carbonaceous thermally conductive fillers and simultaneously controlling the volume resistivity, thermal conductivity, S2, and S1, the black thermally conductive / conductive tailing tape maintains the necessary insulation boundary while improving outer ring heat diffusion, reducing the risk of short circuits caused by excessive interconnection of fillers such as carbon black, graphite, or carbon nanotubes. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a schematic diagram of the outer ring finishing area and composite finishing structure of the all-pole cylindrical core according to an embodiment of the present invention; Figure 2 for Figure 1 A structural schematic diagram of the cylindrical core with a central all-pole lug from another perspective. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0026] To address the issues of inconsistent use of conventional finishing tape bonding in the outer ring of high-capacity all-tab cylindrical battery cores, including space utilization of the metal finishing layer, radial pre-tensioning of the outer ring, and short-circuit safety boundaries, this invention provides an all-tab cylindrical battery core structure that integrates finishing tape coverage, expansion pre-tensioning, metal finishing layer space utilization, thermally / conductively conductive filler safety boundaries, and edge insulation distances. This structure not only protects the internal space utilization of approximately 5Ah-class 21700 all-tab cylindrical battery cells but also improves drop, vibration, and short-circuit safety and reliability.

[0027] like Figure 1 and Figure 2 As shown, this embodiment of the invention provides a cylindrical core with full tabs, including a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive and negative electrode sheets. The positive electrode sheet, separator, and negative electrode sheet are wound together to form a core, and the axial ends of the positive and negative electrode sheets form a flattened full tab structure. A composite finishing structure is provided in the outer ring of the core, comprising a composite finishing tape and a metal finishing layer. The composite finishing tape and the metal finishing layer are described below: [Composite finishing tape] The composite finishing tape is attached circumferentially to the outer finishing area of ​​the core, serving multiple functions including fixing, heat conduction, and insulation. The composite finishing tape consists of a substrate layer and an adhesive layer. The substrate layer forms the skeleton of the composite finishing tape, providing mechanical strength and dimensional stability; the adhesive layer is responsible for firmly bonding the composite finishing tape to the outer ring of the core and the surface of the metal finishing layer.

[0028] The coverage arc length of the composite finishing tape along the winding direction is L1 (mm); the width of the composite finishing tape is W1 (mm); the thickness of the composite finishing tape before application is t1 (mm); the thickness change rate of the composite finishing tape after being immersed in electrolyte at 25℃ for 24 hours and heat-treated at 80℃ for 30 minutes is E1 (E1 is a decimal); the maximum outer diameter of the core in the finishing area is D1 (mm); the core height is H1 (mm); half the difference between the inner diameter of the shell and the maximum outer diameter of the core is the radial allowance G1 (mm). The finishing coverage-radial pretensioning coordination coefficient Kp is defined as: Kp = (L1 / (π×D1))×(W1 / H1)×(t1×(1+E1) / G1), and 0.015≤Kp≤0.045, specifically it can be 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, etc.

[0029] In a preferred embodiment, Kp is 0.020~0.045, preferably 0.025~0.040. By optimizing the value of Kp, a better balance between fixed reliability and spatial adaptability can be achieved. L1 is 35mm~120mm, such as 35mm, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm, 100mm, 105mm, 110mm, 115mm, 120mm, etc. W1 is 3.0mm~12.0mm, such as 3.0mm, 4.0mm, 5.0mm, 6.0mm, 7.0mm, 8.0mm, 9.0mm, 10.0mm, 11.0mm, 12.0mm, etc. t1 is 0.020mm~0.120mm, such as 0.020mm, 0.030mm, 0.040mm, 0.050mm, 0.060mm, 0.070mm, 0.080mm, 0.090mm, 0.100mm, 0.110mm, 0.120mm, etc. E1 is 0.05~0.80, specifically 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, etc. D1 is 20.20mm~20.70mm, and can be 20.20mm, 20.25mm, 20.30mm, 20.35mm, 20.40mm, 20.45mm, 20.50mm, 20.55mm, 20.60mm, 20.65mm, 20.70mm, etc. H1 is 64.5mm~67.5mm, and can be 64.5mm, 65.0mm, 65.5mm, 66.0mm, 66.5mm, 67.0mm, 67.5mm, etc. G1 is 0.03mm~0.35mm, such as 0.03mm, 0.05mm, 0.08mm, 0.10mm, 0.12mm, 0.15mm, 0.18mm, 0.20mm, 0.22mm, 0.25mm, 0.28mm, 0.30mm, 0.32mm, 0.35mm, etc.

[0030] It should be noted that Kp relates the coverage arc length, width, thickness, expansion rate, core outer diameter, core height, and radial allowance within the shell of the composite finishing tape. It is used to characterize the contribution of the tape coverage area and expansion pretension to the outer ring finishing fixation. This invention does not simply increase the tape thickness or the tape coverage length; instead, it uses Kp to constrain the coverage arc length, tape width, expansion rate, and radial allowance within the shell, ensuring that the outer ring finishing fixation and radial pretension are matched. Adjusting the value of Kp can reduce axial displacement of the core and radial loosening of the outer ring after a drop.

[0031] In some embodiments, the substrate layer of the composite finishing tape is selected from at least one of polyimide (PI), polyethylene terephthalate (PE1), polypropylene (PP), polyethylene (PE), aramid paper, and polyamide-imide (PAI), and the main material of the substrate layer can be any one or more of the above. The adhesive layer of the composite finishing tape is selected from at least one of acrylic pressure-sensitive adhesives, silicone rubber pressure-sensitive adhesives, polyurethane adhesives, and epoxy-modified adhesives, and the main material of the adhesive layer can be any one or more of the above. Both the substrate layer and the main material of the adhesive layer are commercially available materials; for example, the epoxy-modified adhesive can be a commercially available epoxy-modified adhesive, and the specific modification method is not limited.

[0032] Furthermore, a carbonaceous thermally conductive filler is dispersed in the substrate layer and / or adhesive layer to impart thermal conductivity to the composite finishing tape. The carbonaceous thermally conductive filler can be located in the substrate layer, the adhesive layer, or both. In some embodiments, the carbonaceous thermally conductive filler is selected from at least one of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, and acetylene black, and can be any one or more of the above. The mass content of the carbonaceous thermally conductive filler in the composite finishing tape is 2wt% to 25wt%, specifically 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, etc., preferably 5wt% to 15wt%. When the content of carbonaceous thermally conductive filler is less than 2 wt%, it is difficult to form an effective thermally conductive network inside the tape, making it difficult to achieve the specified in-plane thermal conductivity and failing to effectively improve the thermal diffusion of the outer ring. When the content of carbonaceous thermally conductive filler is greater than 25 wt%, the filler particles easily form conductive paths inside the tape, leading to a decrease in volume resistivity, weakening the insulation safety boundary, and increasing the risk of short circuits. Controlling the content of carbonaceous thermally conductive filler within the preferred range of 5 wt% to 15 wt% can balance thermal conductivity and insulation performance.

[0033] In some embodiments, the composite finishing tape further includes an insulating and thermally conductive filler, which is dispersed in the substrate layer and / or adhesive layer. The insulating and thermally conductive filler may be present in one or both layers, and an insulating barrier region may be formed near the end of the metal finishing layer and the edge of the active material layer of the negative electrode sheet. Carbonaceous thermally conductive filler may be concentrated in the central thermally conductive filler enrichment region of the composite finishing tape, while the insulating and thermally conductive filler can improve the insulation and thermal conductivity buffering capacity in the region adjacent to the metal end and the electrode edge. Introducing the insulating and thermally conductive filler can further optimize the thermal conductivity and insulation performance. The insulating and thermally conductive filler is selected from at least one of alumina, boehmite, boron nitride, magnesium oxide, and silicon oxide; any one or more of these can be used. By controlling the amount of insulating and thermally conductive filler, the thermal conductivity and other parameters of the composite finishing tape can meet the requirements.

[0034] Furthermore, the in-plane thermal conductivity of the composite finishing tape is 0.30 W / (m·K) to 3.00 W / (m·K), such as 0.30 W / (m·K), 0.50 W / (m·K), 0.80 W / (m·K), 1.00 W / (m·K), 1.20 W / (m·K), 1.50 W / (m·K), 1.80 W / (m·K), 2.00 W / (m·K), 2.20 W / (m·K), 2.50 W / (m·K), 2.80 W / (m·K), 3.00 W / (m·K), etc. The thermal conductivity in the thickness direction is 0.15 W / (m·K) to 1.20 W / (m·K), such as 0.15 W / (m·K), 0.20 W / (m·K), 0.30 W / (m·K), 0.40 W / (m·K), 0.50 W / (m·K), 0.60 W / (m·K), 0.70 W / (m·K), 0.80 W / (m·K), 0.90 W / (m·K), 1.00 W / (m·K), 1.10 W / (m·K), 1.20 W / (m·K), etc.

[0035] In some embodiments, the composite finishing tape further includes an expanding adhesive layer, which is disposed between the substrate layer and the adhesive layer, or on the side of the substrate layer away from the adhesive layer, with the adhesive layer located near the outer ring of the core. The expanding adhesive layer provides radial preload after electrolyte wetting, heat treatment, or pressure rebound. After the expanding adhesive layer is wetted in electrolyte at 25°C for 24 hours and heat-treated at 80°C for 30 minutes, the thickness change rate E1 of the composite finishing tape is 0.10~0.60. Specifically, E1 can be 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, etc. If E1 is too low, it cannot compensate for the outer ring gap; if it is too high, it will cause local compression or push on the metal end. Therefore, it needs to be controlled by Kp along with parameters such as t1 and G1.

[0036] Furthermore, the expanding adhesive layer contains at least one of the following: liquid-absorbing and expanding microparticles, thermally expanding microspheres, elastomer microporous structures, and foamed polymer microdomains. The liquid-absorbing and expanding microparticles expand in volume after absorbing electrolyte; the thermally expanding microspheres expand during heat treatment or when the battery cell heats up; the elastomer microporous structures and foamed polymer microdomains provide pre-tightening force through compressive rebound. Specifically, the liquid-absorbing and expanding microparticles can be cross-linked polyacrylate microparticles, cross-linked polyacrylic acid microparticles, or polyacrylamide liquid-absorbing microparticles, etc. The thermally expanding microspheres can specifically be thermally expanding microspheres with polyvinylidene chloride, polyacrylonitrile, or copolymers thereof as the shell and low-boiling-point hydrocarbons as the core material, etc. The elastomer microporous structure can be formed by introducing an extractable pore-forming agent into silicone rubber, polyurethane, or acrylate elastomers followed by extraction, or by physical foaming. The foamed polymer microdomains can be formed during adhesive coating and curing using thermally decomposing foaming agents, phase separation, or microsphere pre-foaming.

[0037] The volume resistivity of the composite finishing tape at 25℃ is 1.0×10⁻⁶. 4 Ω·cm ~ 1.0×10 10 Ω·cm, specifically 1.0 × 10 4 Ω·cm, 5.0×10 4 Ω·cm, 1.0×10 5 Ω·cm, 5.0×10 5 Ω·cm, 1.0×10 6 Ω·cm, 5.0×10 6 Ω·cm, 1.0×10 7 Ω·cm, 5.0×10 7 Ω·cm, 1.0×10 8 Ω·cm, 5.0×10 8 Ω·cm, 1.0×10 9 Ω·cm, 5.0×10 9 Ω·cm, 1.0×10 10 Ω·cm, etc. In-plane thermal conductivity is greater than or equal to 0.30 W / (m·K), specifically 0.30 W / (m·K), 0.50 W / (m·K), 0.80 W / (m·K), 1.00 W / (m·K), 1.20 W / (m·K), 1.50 W / (m·K), 1.80 W / (m·K), 2.00 W / (m·K), 2.20 W / (m·K), 2.50 W / (m·K), 2.80 W / (m·K), 3.00 W / (m·K), etc.

[0038] [Metallic Finishing Layer] The metal finishing layer is located at or adjacent to the outermost ring of the negative electrode sheet, and at least a portion of the metal finishing layer is covered by composite finishing tape. "Adjacent to" in "adjacent to the outermost ring of the negative electrode sheet" means that the distance from the finishing end of the outermost ring of the negative electrode sheet along the winding direction is no more than 10 mm, or the position overlaps with the outermost ring of the negative electrode sheet.

[0039] In some embodiments, the material of the metal finishing layer is selected from at least one of copper foil, nickel-plated copper foil, carbon-plated copper foil, aluminum foil, stainless steel foil, nickel foil, and copper-polymer composite foil, and the material of the metal finishing layer can be any one or more of the above.

[0040] The coverage length of the metal finishing layer along the winding direction is L2, in mm; the thickness of the metal finishing layer before application is t2, in mm; the metal finishing-space utilization synergy coefficient Km is defined as: Km = (L2 / L1) × (t2 / t1) × (G1 / (t1 × (1+E1))), and 0.15 ≤ Km ≤ 0.95. Km can specifically be 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, etc.

[0041] It should be noted that Km relates the coverage length of the metal termination layer, the thickness of the metal layer, the thickness of the tape, the tape expansion rate, and the radial margin, and is used to characterize the matching relationship between the metal layer in saving space, assisting heat conduction, and not occupying too much radial margin. This invention uses Km to constrain the coverage length and thickness of the metal termination layer, so that the copper foil or metal composite layer can save space and assist heat diffusion in the outer ring termination, while avoiding excessive radial margin occupation or the introduction of end short-circuit risks due to excessively thick or long metal layers.

[0042] In a preferred embodiment, the thickness t2 of the metal finishing layer is 0.004mm to 0.030mm, such as 0.004mm, 0.006mm, 0.008mm, 0.010mm, 0.012mm, 0.015mm, 0.018mm, 0.020mm, 0.025mm, 0.030mm, etc., preferably 0.006mm to 0.015mm. The coverage length L2 of the metal finishing layer along the winding direction is 30mm to 140mm, such as 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm, 100mm, 110mm, 120mm, 130mm, 140mm, etc. The ratio of L2 to the coverage arc length L1 of the composite finishing tape along the winding direction, L2 / L1, is 0.50~1.30, such as 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, etc.

[0043] There is an insulating clearance distance S2 between the end of the metal finishing layer and the outer edge of the composite finishing tape, and an edge insulating distance S1 between the conductive filler enrichment area of ​​the composite finishing tape and the edge of the active material layer of the negative electrode sheet. Both S2 and S1 are greater than or equal to 0.5 mm, such as 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, etc. S2 is greater than or equal to 0.6 times S1, and S2 is 0.5mm to 6.0mm. Specifically, S2 can be 0.5mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm, 4.5mm, 5.0mm, 5.5mm, 6.0mm, etc.; S1 is 0.5mm to 6.0mm, such as 0.5mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm, 4.5mm, 5.0mm, 5.5mm, 6.0mm, etc.

[0044] When the volume resistivity of the composite finishing tape is less than 1.0×10 6 At Ω·cm, both S2 and S1 are greater than or equal to 1.0 mm to provide a wider insulation safety boundary.

[0045] In some embodiments, the width of the metal finishing layer along the core axis is less than or equal to the width of the composite finishing tape, and at least one axial edge of the metal finishing layer is recessed by 0.5mm to 5.0mm relative to the corresponding axial edge of the composite finishing tape. Specifically, the recessed amount can be 0.5mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm, 4.5mm, 5.0mm, etc. The recessed axial edge of the metal finishing layer relative to the tape edge ensures that the metal finishing layer is completely covered by the tape in the axial direction, preventing exposed metal edges and thus reducing the risk of contact with the housing or other conductive components.

[0046] This invention, through the structural synergy between the composite finishing tape, the metal finishing layer, and the expanding adhesive layer, ensures the stability of the outer ring of the core after drops and vibrations. Simultaneously, it controls the balance between thermal diffusion and short-circuit risk through the carbonaceous thermally conductive filler and the edge insulation clearance distance. Furthermore, this invention defines the volume resistivity and thermal conductivity of the composite finishing tape, as well as the insulation clearance distance S2 between the end of the metal finishing layer and the outer edge of the tape, and the tape edge insulation distance S1 between the conductive filler-rich area and the edge of the active material layer. These limitations allow the composite finishing tape to maintain sufficient insulation safety boundaries while possessing a certain degree of thermal diffusion capability, avoiding short-circuit risks caused by the thermally / conductive filler or the end of the metal finishing layer.

[0047] The core provided in this invention can be used for 4.9Ah to 5.2Ah cylindrical lithium-ion cells of model 21650 or 21700. After being dropped once from a height of 1.5m in six directions at 100% SOC and 25℃, the axial displacement of the core relative to the shell is less than or equal to 0.30mm, and the radial looseness of the core's end area is less than or equal to 0.15mm. After 2 hours of sweeping vibration at 10Hz to 55Hz, the peel length of the composite end tape is less than or equal to 10% of its covered arc length L1. This demonstrates that through the synergistic constraint of Kp and Km, the composite end structure can maintain the integrity of the outer ring of the core under harsh mechanical abuse conditions, preventing core movement and outer ring loosening, thereby ensuring the safety and reliability of the battery cell.

[0048] When determining whether an existing battery cell adopts the composite finishing structure provided in this embodiment of the invention, the following steps can be used for reverse identification: (1) Perform micro-focus X-ray CT detection on the finished cylindrical lithium-ion battery cell to identify the finishing position of the outer ring of the core, the area covered by the finishing tape, and the relative position of the metal finishing layer; (2) Disassemble the finished cylindrical lithium-ion battery cell in an inert atmosphere, unfold the core, and measure the coverage arc length L1, width W1, and thickness t1 of the composite finishing tape, as well as the coverage length L2 and thickness t2 of the metal finishing layer; (3) Identify the carbonaceous thermally conductive filler in the composite finishing tape and the metal element composition of the metal finishing layer through cross-sectional SEM / EDS; (4) Identify the composition of the composite finishing tape and the metal element composition of the metal finishing layer through FTIR, DSC, and TGA identifies the composition of the substrate layer, adhesive layer and filler of the composite finishing tape; (5) obtain the thickness change rate E1 of the composite finishing tape by immersion in electrolyte at 25°C for 24 hours and heat treatment at 80°C for 30 minutes; (6) obtain the electrical and thermal parameters of the composite finishing tape by thickness direction volume resistivity test and transient plane heat source method test; (7) determine whether the finished cylindrical lithium-ion battery cell falls within the corresponding protection range according to Kp, Km, S2 and S1 defined in the present invention embodiment.

[0049] In addition, the axial displacement, radial loosening amount, and peeling length of the composite finishing tape can be retested after the finished cylindrical lithium-ion cells are subjected to drop or vibration treatment, and the retest results can be used as an auxiliary basis for judging the anti-loosening performance.

[0050] This invention also provides a lithium-ion battery, including the aforementioned all-tab cylindrical core, which is housed in a cylindrical shell and forms a cylindrical lithium-ion battery together with a cap assembly, electrolyte, and insulating components. The battery form is not limited and can be a battery pack, module, or other similar form.

[0051] Tests showed that the cylindrical lithium-ion battery had an AC internal resistance of 2.4 mΩ to 3.3 mΩ at 25℃ and 30% SOC, and a 10s DCR of 7.0 mΩ to 10.5 mΩ at 25℃ and 100% SOC. This indicates that the composite tail structure did not negatively affect the battery's internal resistance, and that the metal tail layer and thermally conductive tape did not damage the existing current collector network, and facilitated the circumferential diffusion of heat from the outer ring.

[0052] This invention also provides an electrical device including the aforementioned lithium-ion battery, which is used to provide power.

[0053] The terminology and test methods for variables in the embodiments of this invention are summarized as follows: "Full-tab cylindrical winding core" refers to a cylindrical winding body in which the positive and negative electrode sheets are flattened, pressed, or have an equivalent full-tab current collection structure at their axial ends. For 21700 cylindrical cells, the core height H1 is typically 64.5 mm to 67.5 mm, and the maximum outer diameter D1 is typically 20.20 mm to 20.70 mm.

[0054] "Outer ring finishing area" refers to the outer peripheral area where the core winding ends, including the diaphragm finishing section, the negative electrode outer ring finishing section, the metal finishing layer, and the tape or composite tape used to fix the outer ring.

[0055] "Composite finishing tape" refers to a strip-like structure that is attached to the outer finishing area of ​​the core and includes both a substrate layer and an adhesive layer. This tape can be a single-layer tape or a multi-layer composite structure consisting of a substrate layer, an adhesive layer, an expanding adhesive layer, a thermally conductive filler layer, an insulating covering layer, or a release residue layer.

[0056] "Carbon-based thermally conductive fillers" include carbon materials such as carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, and acetylene black. These fillers can improve the blackness and thermal diffusion capacity of tapes, but their content and connectivity need to be matched with the volume resistivity and edge insulation distance.

[0057] "Metal finishing layer" refers to a metal layer located at or near the outermost ring of the negative electrode sheet, used for finishing support, space saving, or heat diffusion. The metal finishing layer can be a copper foil finishing layer formed by extending the negative electrode copper foil, or it can be a separately attached copper foil, nickel-plated copper foil, carbon-plated copper foil, nickel foil, stainless steel foil, or metal-polymer composite layer.

[0058] The coverage arc length L1 was measured after the core was disassembled and unfolded under an inert atmosphere. The specific steps were as follows: the outer ring of the core was unfolded to a flat surface without stretching the tape. Using an image measuring instrument with a resolution of at least 0.01 mm, the continuous length of the composite finishing tape bonded to the outer ring of the core was measured along the winding direction. Measurements were taken at three axial positions (upper, middle, and lower) for the same tape, and the arithmetic mean of the three measurements was taken as L1. The tape width W1 was measured along the core axial direction using the same image measuring instrument, at the left, middle, and right ends of the tape, and the arithmetic mean of the three measurements was taken as W1.

[0059] The tape thickness t1 was measured using a cross-sectional SEM image after cryo-ion beam cross-section preparation. The specific steps were as follows: a sample containing complete tape layers was cut from the end region, cryo-fixed, and then polished using an ion beam. Cross-sectional images were acquired at 500x to 2000x magnification. The total thickness from the outer surface of the tape to the interface between the tape and the outer ring of the core was measured at at least five evenly distributed locations, and the average value was taken as t1. When the tape has a multi-layer structure, t1 is the total thickness of the substrate layer, adhesive layer, filler layer, and expanding adhesive layer. The thickness t2 of the metal end layer was measured using the same cross-sectional SEM image, with measurements taken at at least five locations within the continuous area of ​​the metal layer, and the average value was taken.

[0060] In this specification, t2 refers to the initial thickness of the metal finishing layer before it is applied to the finishing area of ​​the core. The metal finishing layer does not have the thickness change characterized by liquid absorption and heat treatment as represented by E1, so t2 is not converted to E1.

[0061] The thickness change rate E1 was determined using a fixed electrolyte immersion-heat treatment test. The specific steps were as follows: three 30mm × 10mm samples were cut from the composite finishing tape, and the initial thickness t0 was measured in an environment of 25℃ with a dew point not exceeding -40℃; the samples were then immersed in an electrolyte solution of the same system as the battery cell and left to stand at 25℃ for 24 hours; after removal, the surface free liquid was gently removed with lint-free paper without squeezing the adhesive layer; subsequently, the samples were heat-treated in an 80℃ oven for 30 minutes, and then cooled in a sealed environment at 25℃ for 30 minutes, and the thickness t1 after treatment was measured. The thickness change rate of a single sample was calculated as E1 = (t1 - t0) / t0, and the arithmetic mean of the three samples was taken as E1.

[0062] The maximum outer diameter D1, core height H1, and radial allowance G1 of the core were measured using microfocus X-ray CT. The specific steps were as follows: the finished battery cell was fixed on the CT stage, and the cross-section and axial section were reconstructed using the angle of the finishing tape as a reference; three cross-sections (upper, middle, and lower) were selected at the height of the finishing area, and the outer diameter of the core's circumscribed circle was measured for each, with the maximum value taken as D1; ​​the maximum distance between the outer boundaries of the flattened tabs at both ends of the core was measured in the axial section as H1; the inner diameter Di of the housing was measured in the same cross-section, and the radial allowance was calculated using G1 = (Di - D1) / 2. If the battery cell had been disassembled, the inner diameter Di of the housing was measured from the housing cross-sectional image, and D1 was still based on the CT measurement before disassembly.

[0063] The length L2 of the metal finishing layer was measured using an image after disassembly and unfolding. The specific steps were as follows: unfold the outermost finishing section of the negative electrode, identify the area where the copper foil, plating metal, or metal composite layer is continuously present along the winding direction; use an image measuring instrument to measure the length of this continuous area along the winding direction, measuring once at each of the three axial positions (upper, middle, and lower) of the metal layer, and taking the average value as L2. S2 is the minimum distance from the end of the metal finishing layer to the outer edge of the composite finishing tape, and S1 is the minimum distance from the conductive filler-rich area in the composite finishing tape to the edge of the negative electrode active material layer; both S2 and S1 were measured using an image measuring instrument in the unfolded image, and the minimum value among the three candidate minimum distances was taken as the result.

[0064] Volume resistivity was measured using the thickness-direction high-resistivity method. The specific steps were as follows: three circular samples with a diameter of 20 mm were cut from the composite finishing tape and placed in an environment at 25℃ and relative humidity below 50% for 2 hours; the effective area A of the upper and lower electrodes was 3.14 cm². 2 A high-resistivity meter was used, and the stable resistance R was read after applying a 500V DC voltage for 60 seconds. After measuring the sample thickness t, the volume resistivity was calculated using ρv=R×A / t, and the geometric average of three samples was taken. In-plane thermal conductivity was tested using the transient planar heat source method. The sample was a tape stack of no less than 30mm×30mm, the test temperature was 25℃, and the sensor clamping pressure was 0.05MPa to 0.10MPa. The in-plane thermal conductivity output by the instrument was the average of three measurements.

[0065] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0066] The materials and preparation processes used in the following examples and comparative examples are as follows: In this embodiment, a 21700 cylindrical lithium-ion cell was used as the reference. The positive electrode active material was a layered high-nickel lithium transition metal oxide with a nickel content of approximately 90 mol%. The positive electrode conductive agent included conductive carbon black and carbon nanotubes. The positive electrode binder was polyvinylidene fluoride, and the solvent was N-methylpyrrolidone. After stirring and degassing, the positive electrode slurry was coated on both sides of an aluminum current collector with a thickness of approximately 12 μm. After drying, rolling, and slitting, the positive electrode sheet was formed. The surface density of the reference positive electrode was taken as 12.7 mg / cm³. 2 ~13.6mg / cm 2 The thickness of the positive electrode sheet can be from 87μm to 91μm.

[0067] The negative electrode active material includes artificial graphite and silicon carbide materials; the negative electrode conductive agent includes conductive carbon black and carbon nanotubes; the binder includes sodium carboxymethyl cellulose and styrene-butadiene rubber; and the solvent is deionized water. The negative electrode slurry, after stirring and degassing, is coated onto both sides of the copper current collector, and then dried, rolled, and slit to form the negative electrode sheet. The thickness of the reference negative electrode copper foil can be 6μm to 8μm, and the thickness of the negative electrode sheet can be 84μm to 88μm.

[0068] The diaphragm can be made of polyethylene or polypropylene, and can be coated with boehmite or alumina ceramic on at least one side surface.

[0069] The electrolyte can be made by dissolving LiPF6 in a carbonate mixed solvent and adding fluoroethylene carbonate, sulfonyl lactone, sulfate, boron-containing additives or other film-forming additives.

[0070] During winding, the positive electrode sheet, separator, and negative electrode sheet are wound into a cylindrical core according to a predetermined alignment. A metal termination layer is provided at the end of the winding, and a composite termination tape is attached to the outer termination area. Subsequently, the axial ends of the positive and negative electrodes are flattened, inserted into the cylindrical housing, and the current collector welding, cap connection, grooving, liquid injection, settling, formation, aging, and capacity testing are completed. When attaching the composite termination tape, it should cover at least a portion of the metal termination layer and ensure an insulating clearance distance between the end of the metal termination layer and the edge of the tape.

[0071] Example 1 Example 1 provides a 21700 all-tab cylindrical battery cell structure with a black composite finishing tape and the outermost copper foil of the negative electrode visible from the reverse side. The cell has a core height H1 of 66.1 mm, a maximum outer diameter D1 of 20.46 mm in the finishing area, a negative electrode copper foil thickness t2 of 0.008 mm, and a metal finishing layer at the outermost copper foil of the negative electrode. The composite finishing tape is black, the substrate layer is a polyimide / polyester composite film (0.025 mm thick), and the adhesive layer is an acrylic pressure-sensitive adhesive (0.015 mm thick), containing carbon black and a small amount of graphite thermally conductive filler. The composite finishing tape has a coverage arc length L1 of 64 mm, a width W1 of 6.0 mm, a pre-attachment thickness t1 of 0.050 mm, a thickness change rate E1 of 0.25, a radial allowance G1 of 0.18 mm, and a metal finishing layer coverage length L2 of 62 mm. Calculations show that Kp is approximately 0.0314 and Km is approximately 0.4464. S2 is 1.2 mm, S1 is 1.5 mm, and the indentation of the metal finishing layer relative to the two axial edges of the composite finishing tape is 1.0 mm. The in-plane thermal conductivity of the composite finishing tape is 0.85 W / (m·K), the thickness-direction thermal conductivity is 0.35 W / (m·K), and the volume resistivity is 1.0 × 10⁻⁶. 6 Ω·cm. In this structure, the composite finishing tape covers the end of the metal finishing layer, and the adhesive layer absorbs liquid, expands, and compresses to rebound, forming a radial pretension on the outer ring of the core.

[0072] In Example 1, the substrate layer is a polyimide / polyethylene terephthalate composite film, wherein the polyimide resin is selected with a weight-average molecular weight of 8 × 10⁻⁶. 4 ~1.5×10 5The intrinsic viscosity of the aromatic polyimide and polyethylene terephthalate can be 0.65–0.75 dL / g. The polyimide layer thickness is 0.012 mm, and the polyethylene terephthalate layer thickness is 0.013 mm.

[0073] An expansion layer is disposed between the substrate layer and the adhesive layer, and its thickness after curing is preset to 0.010 mm. The expansion layer contains cross-linked polyvinylidene fluoride-hexafluoropropylene liquid-absorbing and expanding microparticles, the D50 of which is 2-5 μm, accounting for 10 wt% of the solid component of the expansion layer.

[0074] The adhesive layer is a self-formulated acrylic pressure-sensitive adhesive layer, located on the side closest to the core, with a cured thickness of 0.015 mm. The acrylic resin is obtained by copolymerizing butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, acrylic acid, and hydroxyethyl acrylate in a mass ratio of 55:25:15:3:2, with a weight-average molecular weight of 4 × 10⁻⁶. 5 ~8×10 5 .

[0075] Based on the solid components of the adhesive layer, the mass ratio of acrylic resin, carbon black, graphite, and crosslinking agent can be 91:7:1:1. Specifically, the mass ratio of carbon black to graphite is 7:1, and the total addition amount is 8 wt% of the solid components of the adhesive layer, i.e., 7 wt% carbon black and 1 wt% graphite. The above components are dispersed at 1200–1800 rpm for 20–30 min, vacuum degassed for 5–10 min, and then coated onto the surface of the expanded layer. The mixture is then cured at 80°C for 20–40 min to form the adhesive layer.

[0076] Under the conditions of 25±2℃ and static contact with electrolyte for 24h, the thickness change rate E1 of the composite finishing tape is 0.25.

[0077] The basic cathode formulation in this embodiment is as follows: 97.25 wt% high-nickel layered lithium transition metal oxide cathode active material, 1.50 wt% conductive carbon black, 0.10 wt% carbon nanotubes, and 1.15 wt% polyvinylidene fluoride. The cathode slurry is prepared using N-methylpyrrolidone as a solvent. The cathode slurry is coated on both sides of a 12 μm thick aluminum foil, dried, and then rolled to a compaction density of approximately 3.48 g / cm³. 3 The positive electrode sheet is approximately 87 μm thick and has a single-sided areal density of approximately 12.7 mg / cm³. 2 The cutting width is approximately 60mm, and the effective length is approximately 1686mm.

[0078] The basic anode formulation in this embodiment is as follows: 82.95 wt% artificial graphite, 13.50 wt% silicon-carbon composite material, 0.50 wt% conductive carbon black, 0.25 wt% carbon nanotubes, 1.10 wt% sodium carboxymethyl cellulose, and 1.70 wt% styrene-butadiene rubber. The anode slurry is prepared using deionized water as the solvent. The anode slurry is coated on both sides of a copper foil with a thickness of approximately 8 μm, dried, and then rolled to a compaction density of approximately 1.53 g / cm³. 3 The negative electrode sheet is approximately 86.7 μm thick, and the surface density on the concave side is approximately 5.45 mg / cm³. 2 The surface density of a convex surface is approximately 5.48 mg / cm³. 2 The effective length of the first side of the negative electrode is approximately 1719 mm, and the effective length of the second side is approximately 1661 mm.

[0079] The diaphragm in this embodiment is a composite diaphragm consisting of a wet-process polyethylene base membrane and a single-sided boehmite ceramic coating. The base membrane thickness is approximately 7 μm, the ceramic coating thickness is approximately 2 μm, and the total diaphragm thickness is approximately 9 μm to 10 μm, with the ceramic coating facing the negative electrode side. The electrolyte formulation consists of 1.1 mol / L LiPF6 dissolved in a carbonate mixed solvent with an EC / EMC / DEC volume ratio of 3:5:2, with the addition of 1.0 wt% fluoroethylene carbonate, 0.5 wt% vinylene carbonate, and 1.0 wt% 1,3-propanesulfonyl lactone as film-forming and safety additives.

[0080] During preparation, the positive electrode sheet, negative electrode sheet, and separator are first cut separately. Then, the positive electrode sheet, separator, and negative electrode sheet are wound into a cylindrical core under a predetermined tension, leaving the outermost copper foil tail section of the negative electrode as a metal tail layer. Subsequently, black composite tail tape is attached to the tail area of ​​the outer ring of the core, covering the end of the copper foil tail section and ensuring that S2 and S1 meet the above values. Then, the axial ends of the positive and negative electrodes are flattened, and after being installed in the casing, current collector welding, cap welding, grooving, liquid injection, standing, formation, aging, and capacity testing are performed. Formation can be performed by pre-charging to 3.0V with a small current at 25°C, then charging to 4.2V in stages from 0.1C to 0.3C and maintaining constant voltage cutoff. After capacity testing, a 21700 full-tab cylindrical lithium-ion cell with an approximate 5Ah capacity is obtained.

[0081] Example 2 The difference between this embodiment and Embodiment 1 is that by adjusting the thickness of the composite substrate layer and the amount of adhesive coating to a total tape thickness of 0.035mm, the thickness t1 of the composite finishing tape changes from 0.050mm to 0.035mm; otherwise, it is the same as Embodiment 1.

[0082] Example 3 The difference between this embodiment and Embodiment 1 is that by adjusting the thickness of the substrate layer and the amount of the expanding adhesive layer to a total tape thickness of 0.070 mm, the thickness t1 of the composite finishing tape changes from 0.050 mm to 0.070 mm; otherwise, it is the same as Embodiment 1.

[0083] Example 4 The difference between this embodiment and Embodiment 1 is that by adjusting the tape cutting width to 4.5mm, the width W1 of the composite finishing tape changes from 6.0mm to 4.5mm; otherwise, it is the same as Embodiment 1.

[0084] Example 5 The difference between this embodiment and Embodiment 1 is that by adjusting the tape cutting width to 8.5mm, the width W1 of the composite finishing tape changes from 6.0mm to 8.5mm; otherwise, it is the same as Embodiment 1.

[0085] Example 6 The difference between this embodiment and Embodiment 1 is that by adjusting the start and end positions of the adhesive application to achieve a circumferential coverage of 45mm, the arc length L1 of the composite finishing tape coverage changes from 64mm to 45mm; otherwise, it is the same as Embodiment 1.

[0086] Example 7 The difference between this embodiment and Embodiment 1 is that by adjusting the start and end positions of the adhesive application to achieve 90mm circumferential coverage, the arc length L1 of the composite finishing tape coverage changes from 64mm to 90mm; otherwise, it is the same as Embodiment 1.

[0087] Example 8 The difference between this embodiment and Embodiment 1 is that the amount of carbon black and graphite thermally conductive filler is adjusted to 4 wt%, thus changing the mass content of the carbonaceous thermally conductive filler from 8 wt% to 4 wt%; otherwise, it is the same as Embodiment 1. As a result, the in-plane thermal conductivity of the composite finishing tape changes from 0.85 W / (m·K) to 0.45 W / (m·K).

[0088] When the total amount of carbon black and graphite thermally conductive filler is [value missing], the volume resistivity of the composite finishing tape increases from 1.0 × 10 [value missing]. 6 Ω·cm increased to 5.0×10 7 Ω·cm.

[0089] Example 9 The difference between this embodiment and Embodiment 1 is that the amount of carbon black and graphite thermally conductive filler is adjusted to 15 wt%, thus changing the mass content of the carbonaceous thermally conductive filler from 8 wt% to 15 wt%; otherwise, it is the same as Embodiment 1. As a result, the in-plane thermal conductivity of the composite finishing tape changes from 0.85 W / (m·K) to 1.35 W / (m·K), and the volume resistivity changes from 1.0 × 10⁻⁶. 6 Ω·cm becomes 5.0×10 4Ω·cm.

[0090] Example 10 The difference between this embodiment and Embodiment 1 is that the metal finishing layer material is adjusted to a nickel-plated copper foil with a thickness of 0.006 mm, so that the thickness t2 of the metal finishing layer changes from 0.008 mm to 0.006 mm; otherwise, it is the same as Embodiment 1.

[0091] Example 11 The difference between this embodiment and Embodiment 1 is that by adjusting the length of the outermost copper foil end section of the negative electrode to 95mm, the coverage length L2 of the metal end layer changes from 62mm to 95mm; otherwise, it is the same as Embodiment 1.

[0092] Example 12 The difference between this embodiment and Embodiment 1 is that by adjusting the content of liquid-absorbing and expanding microparticles in the expanding adhesive layer to 18wt%, the thickness change rate E1 of the composite finishing tape changes from 0.25 to 0.45; otherwise, it is the same as Embodiment 1.

[0093] Comparative Example 1 The difference between this comparative example and Example 1 is that the content of the expanded adhesive layer was adjusted to 0 wt%, so that the thickness change rate E1 changed from 0.25 to 0.02; otherwise, it is the same as Example 1.

[0094] Comparative Example 2 The difference between this comparative example and Example 1 is that by adjusting the start and end positions of the adhesive application to a circumferential coverage of 20mm, the arc length L1 of the composite finishing tape coverage changes from 64mm to 20mm; otherwise, it is the same as Example 1.

[0095] Comparative Example 3 The difference between this comparative example and Example 1 is that the material of the finishing tape was adjusted to a transparent polyester tape with a carbon thermally conductive filler content of 0 wt%, thus changing the carbon thermally conductive filler content from 8 wt% to 0 wt%; otherwise, it was the same as Example 1. As a result, the in-plane thermal conductivity changed from 0.85 W / (m·K) to 0.20 W / (m·K).

[0096] Comparative Example 4 The difference between this comparative example and Example 1 is that the carbon black feed amount was adjusted to 30 wt%, thus changing the carbonaceous thermally conductive filler content from 8 wt% to 30 wt%; otherwise, it is the same as Example 1. As a result, a continuous conductive network is formed in the tape, and the volume resistivity increases from 1.0 × 10⁻⁶. 6 The Ω·cm becomes 8.0×10 2 Ω·cm.

[0097] Comparative Example 5 The difference between this comparative example and Example 1 is that the outermost metal termination layer coverage length of the negative electrode is adjusted to 0 mm, thus changing the metal termination layer coverage length L2 from 62 mm to 0 mm; otherwise, it is the same as Example 1. Therefore, the metal termination-space utilization synergy coefficient Km becomes 0.

[0098] Comparative Example 6 The difference between this comparative example and Example 1 is that L2 is changed from 62mm to 140mm by adjusting the length of the metal finishing layer to 140mm without increasing the tape coverage; otherwise, it is the same as Example 1. As a result, the end of the metal layer is exposed, and S2 is changed from 1.2mm to 0.2mm.

[0099] Comparative Example 7 The difference between this comparative example and Example 1 is that the tape adhesion relief distance is adjusted to 0.2mm, so that the tape edge insulation distance S1 changes from 1.5mm to 0.2mm; otherwise, it is the same as Example 1.

[0100] Comparative Example 8 The difference between this comparative example and Example 1 is that the content of thermally expanded microspheres in the expanded adhesive layer is adjusted to 35 wt%, so that the thickness change rate E1 changes from 0.25 to 0.95; otherwise, it is the same as Example 1.

[0101] Experimental Example 1 The performance of the products prepared in the test examples and comparative examples is shown in Table 1.

[0102] The performance testing method is as follows: (1) Test of axial / radial displacement of the core after drop Three 21700 cylindrical lithium-ion cells each prepared in the examples and comparative examples were taken, and the cells were adjusted to 100% SOC and left to stand for 2 hours in an environment of 25±2℃. Before testing, the position of the core relative to the shell was recorded using CT scan, and the axial distance between the top end face of the core and the reference surface of the shell groove, as well as the local gap between the outer periphery of the core and the inner wall of the shell, were measured. Then, the core was dropped freely from a height of 1.5m in six directions, once in each direction, with the drop surface being a steel plate with a thickness of not less than 20mm. After the drops, the core was left to stand for 30 minutes, and then a CT scan was performed again. The axial displacement ΔZa is the absolute value of the difference between the axial reference distance of the core before and after the drop; the radial loosening ΔRr is the maximum change in the local gap of the tail area before and after the drop. The judgment criteria are that ΔZa is not greater than 0.30mm and ΔRr is not greater than 0.15mm.

[0103] (2) Test for loosening of the outer ring and peeling of the finishing tape after vibration Three cells from each batch were taken, adjusted to 50% SOC, and subjected to a sweep vibration test at 25±2℃. The vibration frequency ranged from 10Hz to 55Hz, the sweep rate was 1 oct / min, and the single-axis vibration time was 2 hours, conducted sequentially along the axial direction and two radial directions of the cylinder. ACR, open-circuit voltage, and appearance were recorded before and after vibration. After vibration, the cells were disassembled in an inert atmosphere, the core was unwound, and the peel length Lp of the composite finishing tape was measured. The tape peel rate was calculated as Lp / L1×100%. The judgment criterion was a peel rate not exceeding 10% and no exposed contact marks at the end of the metal finishing layer.

[0104] (3) Test of tape expansion rate and adhesion retention rate after thermal shock A 100mm × 10mm strip was cut from a composite finishing tape of the same structure, and the initial thickness t0 and initial 180° peel strength F0 were measured. The strip was immersed in a reference electrolyte for 24 hours, then removed, and the surface residual liquid was wiped off. It was then kept at 80°C for 30 minutes and cooled to 25°C. The thickness t1 and peel strength F1 after treatment were measured. The thickness change rate E1 was calculated as (t1-t0) / t0, and the adhesion retention rate was calculated as F1 / F0 × 100%. The judgment criteria were that E1 was within the range defined by this invention, and the adhesion retention rate was not less than 70%.

[0105] (4) External shortness, compression and safety auxiliary tests Take a battery cell and adjust it to 100% SOC. Perform an external short-circuit test at 25±2℃. The external short-circuit resistance can be selected as 5mΩ, 10mΩ, 20mΩ, or 50mΩ. The short circuit should continue until the cell surface temperature drops to 10℃ below the peak temperature or for 1 hour. Record the highest temperature, whether fire occurs, whether explosion occurs, and the casing deformation. For the crush test, use a cylindrical indenter or a flat indenter, loading at a speed of 5mm / s. The termination condition is when the pressure reaches 13kN, the deformation reaches 50%, or a safety failure occurs.

[0106] (5) Volume resistivity test of tape A sample of the composite finishing tape was cut, the release layer was removed, and the substrate and adhesive layer were kept intact. The volume resistivity in the thickness direction was measured using a high resistivity meter at 25±2℃ and a relative humidity of 45% to 55%. The sample was cut into a circular piece with a diameter of 20 mm, and the effective electrode area A was 3.14 cm². 2 A 500V DC voltage was applied and held for 60 seconds, after which the stable resistance R was read. The sample thickness t was taken from t1 measured by cross-sectional SEM. The volume resistivity was calculated as ρv = R × A / t, where R is the stable resistance, A is the electrode area, and t is the sample thickness. Three samples were tested in each group, and the geometric mean was taken.

[0107] (6) Thermal conductivity test of tape The in-plane and thickness thermal conductivity of composite tapes were tested using the transient planar heat source method. For thin tape samples, multilayer samples were stacked and tested without introducing air gaps, and the interfacial thermal resistance was corrected using blank substrate stacks. The test temperature was 25℃, and the sensor clamping pressure ranged from 0.05 MPa to 0.10 MPa. Each sample was tested three times, and the average value was taken. The in-plane thermal conductivity was used to evaluate the circumferential heat diffusion capability of the outer ring, and the thickness thermal conductivity was used to evaluate the effect of the tape on the radial heat conduction of the outer ring.

[0108] (7) Re-measurement of the position of the metal finishing layer after disassembly After drop, vibration, or thermal shock tests, discharge the battery cell to below 2.5V and transfer it to an inert atmosphere glove box for disassembly. After opening the housing, record the condition of the outer coil of the core. Unwind the core along the winding direction and measure L2, t2, S2, S1, and whether the metal end layer has warped, shifted, or punctured the adhesive layer. If S2 or S1 is less than 0.5mm, it is determined to be insufficient edge insulation clearance.

[0109] (8) ACR / DCR and temperature rise auxiliary test At 25±2℃, the cell was adjusted to 30% SOC, and the ACR was measured using a 1kHz AC internal resistance meter, repeated three times and the average value was taken. For DCR testing, a 10s pulse discharge was performed at 100% SOC, the voltage difference before and after the pulse was recorded, and the DCR was calculated. The 40A temperature rise test can be used as an auxiliary thermal diffusion evaluation. Before the test, the cell was standardly charged to 100% SOC, and then discharged at a constant current of 40A to the cutoff voltage in an environment of 25±2℃. The maximum surface temperature was recorded using a patch thermocouple or an infrared thermal imager. ACR, DCR, and temperature rise are only auxiliary performance parameters.

[0110] Table 1. Performance test results of the products obtained from the examples and comparative examples.

[0111] As shown in Examples 1 to 3 and Comparative Example 1, the tape thickness and expansion capacity jointly determine the outer ring finishing effect. When the tape thickness is too low, the tape itself does not adequately compensate for the outer ring step, the end of the metal finishing layer, and the diaphragm finishing section. Even if the coverage arc length remains unchanged, the morphological fit and compression rebound provided by the adhesive layer are limited, and the axial displacement and radial loosening of the core will increase after a drop. With an appropriate increase in tape thickness, the substrate layer provides outer ring constraint, and the adhesive layer and expanding adhesive layer provide radial pre-tension, making it less likely for the outer ring to slip relative to the core after an impact. However, excessive tape thickness will occupy radial allowance. If it exceeds the range that the internal assembly and core rebound can withstand, it may cause increased resistance to insertion into the shell or local compression. Therefore, incorporating t1, E1, and G1 into Kp together better reflects the balance between outer ring finishing and space utilization than limiting the tape thickness alone.

[0112] As shown in Examples 1, 6, 7, and Comparative Example 2, the covering arc length L1 mainly affects the fixing range of the finishing tape in the circumferential direction of the outer ring. When L1 is too short, the tape can only fix a local area of ​​the outer ring. During drops and vibrations, the core is prone to outer ring loosening starting from the uncovered area, resulting in an increased peeling rate and radial loosening. Appropriately increasing L1 can expand the bonding area and reduce the probability of outer ring end lifting and metal finishing layer displacement. If L1 is too long, although the anti-loosening ability continues to improve, the tape stack and metal layer stack may form a local thick area in the shell, reducing the radial allowance. Therefore, this invention uses L1 / (π×D1) to characterize the circumferential coverage ratio and incorporates it into Kp and Km, so that the covering arc length can both serve the outer ring fixing and not deviate from the spatial constraints of the 21700 high-fill-density core.

[0113] As shown in Examples 1, 4, and 5, the tape width W1 affects the axial coverage stability of the metal tail layer and the outer ring electrode. When W1 is too low, the tape cannot fully cover the end of the metal tail layer and the axial edge of the outer ring tail area. After a drop impact, peeling start points are easily formed at the edge, resulting in tape edge curling or partial exposure of the metal layer end. When W1 is appropriately increased, the tape can cover a wider outer ring area, the metal layer edge and the diaphragm tail section are more fully constrained, and the axial displacement and peeling rate decrease. However, when W1 is too large, the tape may approach the electrode end edge or the flattened area. If a sufficient clearance distance is not set, it will increase the risk of approaching the exposed metal area. Therefore, this invention incorporates W1 / H1 into Kp and requires S2 and S1 to simultaneously meet the lower limit.

[0114] As shown in Examples 1, 12, Comparative Example 1, and Comparative Example 8, the expansion rate E1 has a significant impact on radial preload. When E1 is too low, the tape relies mainly on the initial adhesive force after application, which cannot compensate for the small gaps in the outer ring of the core after electrolyte wetting, thermal cycling, and mechanical impact. The outer ring is more prone to slippage after a drop. When E1 is within a moderate range, the expanding adhesive layer establishes flexible preload between the outer ring of the core and the shell through liquid absorption expansion, thermal expansion, or pressure rebound, which is beneficial for absorbing drop impact and maintaining the position of the finishing area. When E1 is too high, the expanding adhesive layer may generate excessive radial pressure in local areas, causing the metal finishing layer end to be pushed, the tape edge to curl up, or the outer ring of the core to be locally compacted. Therefore, E1 should not be pursued to be as high as possible, but should be limited by Kp in combination with t1, G1, L1, and W1.

[0115] As demonstrated in Examples 1, 10, 11, Comparative Example 5, and Comparative Example 6, the metal finishing layer contributes to both space utilization and heat diffusion. When the outermost ring of the negative electrode is finished with copper foil or a metal composite layer, the metal layer is thinner and has higher thermal conductivity, enabling it to form a thin finishing support on the outer ring, reducing the radial space occupied by ordinary thick tape stacking, and providing a continuous path for heat diffusion on the outer ring. When the metal layer is too thin or is omitted, the outer ring finishing mainly relies on tape, resulting in decreased space utilization and heat diffusion capacity, and an increased peeling rate after vibration. When the metal layer is too long or the ends are exposed, although the heat diffusion area increases, the metal edge is more likely to approach the active area of ​​the electrode, the shell, or other conductive components, increasing the risk of short circuits. Therefore, this invention defines the relationship between L2, t2, t1, E1, and G1 by Km, and defines the metal end clearance distance by S2.

[0116] As shown in Examples 1, 8, 9, Comparative Example 3, and Comparative Example 4, there are upper and lower limits to the content of carbon black or other thermally / conductively conductive fillers. When the filler content is too low, the tape has a high volume resistivity but insufficient thermal conductivity. The local heat generated in the outer ring tail area is difficult to diffuse circumferentially in time, which may manifest as a localized high temperature rise in high-rate or external short-circuit assisted tests. When the filler content is moderate, the tape still maintains a high volume resistivity, while the in-plane thermal conductivity is improved, which is beneficial for the metal tail layer and the outer ring tape to jointly disperse heat. When the filler content is too high, a continuous conductive network may form between carbon black, graphite, or carbon nanotubes, causing the volume resistivity to drop to an excessively low range. If the tape edge clearance is insufficient, the conductive filler-rich area may become a source of short-circuit risk. Therefore, this invention simultaneously limits the filler content, volume resistivity, thermal conductivity, and S1.

[0117] It should be noted that the comparative examples were not all used to verify Kp or Km individually: Kp of Comparative Example 2 was 0.0098 and Km was 1.4285, Km of Comparative Example 5 was 0, Km of Comparative Example 6 was 1.0080, and Kp of Comparative Example 8 was 0.0490. At least one of them exceeded the corresponding limit range, which is used to illustrate the risks of outer ring fixation, space utilization, or local compression when Kp or Km is mismatched; Comparative Examples 1, 3, 4, and 7 respectively verified independent conditions such as expansion rate, thermally conductive filler, resistivity, and insulation clearance distance, and Kp or Km cannot replace their safety and performance boundaries.

[0118] As demonstrated in Examples 1, 6, and 7, the edge insulation clearance distances S2 and S1 are necessary boundaries for the safe application of thermally / conductive fillers and metal end-layers. If S2 is too small, even if the end of the metal end-layer is covered by tape, it may approach conductive components after a drop or thermal shock due to adhesive flow, edge lifting, or outer ring misalignment. If S1 is too small, the conductive filler-rich area in the tape may approach the edge of the active material layer, turning the tape, which should provide insulation and fixation, into a potential leakage current path. When S2 and S1 are too large, although insulation safety is improved, the usable coverage area decreases, and outer ring fixation and thermal diffusion of the metal layer are affected. Therefore, S2 and S1 need to be matched with the tape volume resistivity, metal layer thickness, and tape width.

[0119] In summary, the present invention provides a cylindrical winding core with multiple tabs, a lithium-ion battery, and an electrical device, which have the following advantages: (1) The present invention does not increase the thickness of the tape alone or increase the coverage length of the tape alone. Instead, it uses Kp to constrain the coverage arc length, tape width, expansion rate and radial allowance inside the shell, so that the outer ring end fixation and radial pre-tightening are in a matching state. This design can reduce the axial displacement of the core and the radial loosening of the outer ring after a drop.

[0120] (2) The present invention uses Km to constrain the coverage length and thickness of the metal tail layer, so that the copper foil or metal composite layer can save space and assist heat diffusion in the outer ring tail, and will not occupy too much radial margin in the shell or introduce the risk of end short circuit due to the metal layer being too thick or the coverage being too long.

[0121] (3) By controlling the content of carbonaceous thermally conductive filler, volume resistivity, thermal conductivity, S2 and S1, this invention enables the black thermally conductive / conductive finishing tape to maintain the necessary insulation boundary while improving the thermal diffusion of the outer ring. This design can reduce the risk of short circuits caused by excessive interconnection of fillers such as carbon black, graphite or carbon nanotubes.

[0122] Furthermore, the core parameters of this invention can all be obtained through CT / X-ray, inert atmosphere disassembly, optical measurement, SEM / EDS, FTIR, DSC, TGA, T2A, volume resistivity, and thermal conductivity tests on finished cylindrical cells, demonstrating strong reverse engineering feasibility. The composite tailing structure described in this invention can be used for reverse engineering from a single unknown finished cylindrical lithium-ion cell using the following methods.

[0123] First, the appearance of the unknown finished battery cell was recorded, including its dimensions, weight, open-circuit voltage, casing polarity, and inkjet printing information. After adjusting the battery cell to a low SOC state suitable for disassembly, non-destructive imaging was performed using microfocus X-ray CT to observe the outer ring end position of the core, the area covered by the end tape, the position of the metal end layer, the inner diameter of the casing, and the outer diameter of the core. The maximum outer diameter D1 of the core end area, the core height H1, and the radial allowance G1 were measured according to the aforementioned CT measurement steps.

[0124] Secondly, the battery cell was disassembled in an inert atmosphere glove box with a water and oxygen content not exceeding 1 ppm. After opening the casing, photographs were taken to record the condition of the outer ring of the core, the color of the tape, the position of the tape coverage, and whether the metal termination layer was visible. The core was gradually unwound along the winding direction, avoiding stretching the tape or damaging the original position of the metal termination layer end. After unwinding, L1, W1, L2, S2, and S1 were measured using an image measuring instrument with a resolution of not less than 0.01 mm. Cross-sectional samples of the tape and metal layer were taken, and t1 and t2 were measured using SEM of the cross-section after cryo-ion beam cross-section preparation.

[0125] Next, material identification was performed on the composite finishing tape. The tape color and Lab* coordinates were recorded using natural light and a spectrophotometer; SEM / EDS was used to analyze carbon enrichment, metallic elements, and inorganic filler elements in the tape cross-section and surface; TGA was used to determine the residual proportions of carbon black, graphite, or inorganic fillers; FTIR was used to identify the polymer types of the substrate layer and adhesive layer; and DSC was used to identify the substrate melting peak, glass transition, and adhesive layer thermal response. If the tape contains thermally expanding microspheres or liquid-absorbing and expanding particles, this can be confirmed through cross-sectional SEM and morphological changes before and after heat treatment.

[0126] Next, the thickness change performance of the tape was tested. The tape sample peeled from the end area was cut into three 30mm×10mm pieces, and the initial thickness t0 was measured. The pieces were immersed in an electrolyte at 25℃ for 24h, removed and gently touched to remove free liquid from the surface, then heat-treated at 80℃ for 30min and cooled at 25℃ for 30min. The thickness t1 after treatment was measured, and the thickness change rate was calculated according to E1=(t1-t0) / t0. The arithmetic mean of the three samples was taken.

[0127] Next, the electrical and thermal properties of the tape were tested. Volume resistivity was measured using the thickness-direction high-resistivity method and calculated using ρv = R × A / t. Thermal conductivity was measured using the transient plane heat source method at a test temperature of 25℃ and a sensor clamping pressure of 0.05 MPa to 0.10 MPa. For carbon-filled tapes, if the volume resistivity is below 1.0 × 10⁻⁶, the thermal conductivity is considered acceptable. 6 For Ω·cm, it is important to verify whether S2 and S1 meet the higher insulation clearance requirements.

[0128] Finally, the measured values ​​of L1, W1, t1, E1, D1, H1, G1, L2, and t2 are substituted into the formulas Kp and Km to determine whether they fall within the scope of this invention. If the same battery cell is further subjected to drop or vibration treatment, the axial displacement, radial loosening, and tape peeling rate of the core can be remeasured as supplementary evidence of the anti-loosening effect.

[0129] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A cylindrical wound core with full tabs, characterized in that, It includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The positive electrode, the separator, and the negative electrode are wound together to form a core. The axial ends of the positive electrode and the negative electrode form a flattened full-tab structure. The outer ring of the core is provided with a composite finishing structure, which includes a composite finishing tape and a metal finishing layer. The composite finishing tape is attached to the outer finishing area along the circumference of the core. The composite finishing tape includes a substrate layer and an adhesive layer, and carbonaceous thermally conductive filler is dispersed in the substrate layer and / or the adhesive layer. The volume resistivity of the composite finishing tape at 25°C is 1.0 × 10⁻⁶. 4 Ω·cm ~ 1.0×10 10 Ω·cm, in-plane thermal conductivity greater than or equal to 0.30 W / (m·K); The metal finishing layer is disposed at or near the outermost ring of the negative electrode sheet, and at least a portion of the metal finishing layer is covered by the composite finishing tape.

2. The all-loop cylindrical core according to claim 1, characterized in that, The composite finishing tape has a coverage arc length L1 along the winding direction, in mm; the width of the composite finishing tape is W1, in mm; the thickness of the composite finishing tape before application is t1, in mm; the thickness change rate of the composite finishing tape after being immersed in an electrolyte at 25°C for 24 hours and heat-treated at 80°C for 30 minutes is E1, where E1 is a decimal; the maximum outer diameter of the core in the finishing area is D1, in mm; the core height is H1, in mm; half the difference between the inner diameter of the shell and the maximum outer diameter of the core is the radial allowance G1, in mm; the finishing coverage-radial pretensioning coordination coefficient Kp is defined as: Kp=(L1 / (π×D1))×(W1 / H1)×(t1×(1+E1) / G1), and 0.015≤Kp≤0.045; The coverage length of the metal finishing layer along the winding direction is L2, in mm; the thickness of the metal finishing layer before application is t2, in mm; the metal finishing-space utilization synergy coefficient Km is defined as: Km = (L2 / L1) × (t2 / t1) × (G1 / (t1 × (1+E1))), and 0.15 ≤ Km ≤ 0.95; The end of the metal finishing layer has an insulation clearance distance S2 between it and the outer edge of the composite finishing tape, and the conductive filler enrichment area of ​​the composite finishing tape has an edge insulation distance S1 between it and the edge of the active material layer of the negative electrode sheet. Both S2 and S1 are greater than or equal to 0.5 mm. Preferably, Kp is 0.020~0.045, more preferably 0.025~0.040; Preferably, L1 is 35mm~120mm; Preferably, W1 is 3.0mm~12.0mm; Preferably, t1 is 0.020mm~0.120mm; Preferably, E1 is 0.05~0.80; Preferably, D1 is 20.20mm~20.70mm; Preferably, H1 is 64.5mm~67.5mm; Preferably, G1 is 0.03mm~0.35mm.

3. The all-loop cylindrical core according to claim 1 or 2, characterized in that, The substrate layer of the composite finishing tape is made of at least one of polyimide, polyethylene terephthalate, polypropylene, polyethylene, aramid paper, and polyamide-imide. And / or, the adhesive layer of the composite finishing tape is selected from at least one of acrylic pressure-sensitive adhesives, silicone rubber pressure-sensitive adhesives, polyurethane adhesives and epoxy modified adhesives; And / or, the carbonaceous thermally conductive filler is selected from at least one of carbon black, conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers and acetylene black; the mass content of the carbonaceous thermally conductive filler in the composite finishing tape is 2wt%~25wt%, preferably 5wt%~15wt%.

4. The all-loop cylindrical winding core according to claim 3, characterized in that, The composite finishing tape also includes an insulating and thermally conductive filler, which is dispersed in the substrate layer and / or the adhesive layer, and can form an insulating barrier region in the area near the end of the metal finishing layer and the edge of the active material layer of the negative electrode sheet; the insulating and thermally conductive filler is selected from at least one of alumina, boehmite, boron nitride, magnesium oxide and silicon oxide. And / or, the composite finishing tape has an in-plane thermal conductivity of 0.30 W / (m·K) to 3.00 W / (m·K) and a thickness direction thermal conductivity of 0.15 W / (m·K) to 1.20 W / (m·K).

5. The all-loop cylindrical winding core according to claim 3, characterized in that, The composite finishing tape further includes an expanding adhesive layer, which is disposed between the substrate layer and the adhesive layer, or on the side of the substrate layer away from the adhesive layer; the adhesive layer is located on the side close to the outer ring of the core. Preferably, after the expanded adhesive layer is immersed in an electrolyte at 25°C for 24 hours and heat-treated at 80°C for 30 minutes, the thickness change rate E1 of the composite finishing tape is 0.10~0.

60. Preferably, the expanding adhesive layer contains at least one of the following: liquid-absorbing expanding microparticles, thermally expanding microspheres, elastomer microporous structures, and foamed polymer microregions.

6. The all-loop cylindrical winding core according to claim 2, characterized in that, The material of the metal finishing layer is selected from at least one of copper foil, nickel-plated copper foil, carbon-plated copper foil, aluminum foil, stainless steel foil, nickel foil, and copper-polymer composite foil; And / or, the thickness t2 of the metal finishing layer is 0.004mm~0.030mm, preferably 0.006mm~0.015mm; And / or, the coverage length L2 of the metal tail layer along the winding direction is 30mm~140mm, and L2 / L1 is 0.50~1.30; And / or, the width of the metal finishing layer along the core axis is less than or equal to the width of the composite finishing tape, and at least one axial edge of the metal finishing layer is recessed by 0.5mm to 5.0mm relative to the corresponding axial edge of the composite finishing tape. And / or, S2 is greater than or equal to 0.6 times S1, and S2 is 0.5mm~6.0mm, S1 is 0.5mm~6.0mm; when the volume resistivity of the composite finishing tape is less than 1.0×10 6 When the value is Ω·cm, both S2 and S1 are greater than or equal to 1.0 mm.

7. The all-loop cylindrical core according to claim 1, characterized in that, The core is used for 21650 or 21700 model cylindrical lithium-ion cells with a capacity of 4.9Ah to 5.2Ah. And / or, after the core is dropped once from a height of 1.5m in six directions at 100% SOC and 25℃, the axial displacement of the core relative to the shell is less than or equal to 0.30mm, and the radial loosening of the core tail area is less than or equal to 0.15mm. And / or, after 2 hours of sweeping vibration at 10Hz to 55Hz, the peel length of the composite finishing tape is less than or equal to 10% of its covering arc length L1.

8. A lithium-ion battery, characterized in that, The invention includes a full-tab cylindrical core as described in any one of claims 1 to 7, wherein the full-tab cylindrical core is housed in a cylindrical housing and forms a cylindrical lithium-ion battery with a cap assembly, an electrolyte, and an insulating component.

9. The lithium-ion battery according to claim 8, characterized in that, The cylindrical lithium-ion battery has an AC internal resistance of 2.4 mΩ to 3.3 mΩ at 1 kHz at 25°C and 30% SOC; and / or a 10 s DCR of 7.0 mΩ to 10.5 mΩ at 25°C and 100% SOC.

10. An electrical appliance, characterized in that, The lithium-ion battery includes any one of claims 8 to 9.